Ovarectomy despite Negative Imaging in Anti-NMDA Receptor Encephalitis: Effective Even Late - Anna-Lena Boeck; Frank Logemann; Terence Krauß; Kais Hussein; Eva Bültmann; Corinna Trebst; Martin Stangel (Case Reports in Neurological Medicine)
Anti-NMDA receptor (NMDAR) encephalitis is an autoimmune antibody-mediated neuropsychiatric disorder. The disorder is known to be associated with ovarian teratoma and predominantly affects young women. Here, we report the case of a 34-year-old woman with anti-NMDAR encephalitis, in which detailed investigations gave no specific hint for an ovarian teratoma. Despite this, and due to a continuous severe clinical syndrome, an ovarectomy was performed and histological examination revealed an occult teratoma. The ovarectomy led to a remarkable improvement even with a long term intensive care treatment for 11 months. The most important lesson to be learned from this instructive case is that even though none of the investigations was indicative for an ovarian teratoma, including an explorative laparoscopy with biopsy, there still may be an occult ovarian teratoma. This shows that tumour search and diagnosis are extremely important in patients presenting with anti-NMDAR encephalitis, and a laparotomy and ovarectomy is justified. Furthermore, removal of the teratoma even 11 months after a very severe course is still therapeutically effective.